Adoption of lib (Lithium Batteries) for hybrid propulsion on small passenger vessel and consequences on damage stability - Ruggiero, Valerio (Edelweiss Applied Science and Technology, 2024)
Nowadays the Hybrid Propulsion is a reality, increasing its diffusion. The main principle is the storing of energy in battery packs to provide energy for the propulsion system of the vessel, aiming the fundament of hybrid propulsion is the use of Li-Ion or Li-Po batteries, with high capability of energy storage (MWh). This good capability has the disadvantage of the explosion risk if exposed to heat. The solutions adopted can impact on damage stability. This paper will analyze the aspects connected with hybrid propulsion in small passenger vessels, considering the State of Art of Rules regarding the fire safety and the possible solutions adopted regarding Lithium batteries. The paper refers to the consequences of adoption of new technology of Lithium batteries developed to be used in maritime application, batteries indicated as “LiB”. The paper is not referring to Lithium metal batteries with the Lithium used as metallic anode and all the consequences on fire risks. The paper is not about the risk of fire due to the battery technology, but is related to the consequences on stability of small vessels if, for security reason a large amount of water is used to cool down the battery packs. The paper will consider the case study of a small passenger ship, examining the general arrangement adopted and the position of the batteries, and the consequences caused by the installation on board of the battery packs. The results will show how the fire safety is important and requires special attention, also in consideration of the various possibilities to contain the fire or prevent the risk of explosion. The aim is to give a suggestion for set new standards for firefighting in presence of large batteries and also to focus on possible problems arising in case of fire on hybrid vessels.